Phillipsastreid corals from the Frasnian (Upper Devonian) of Western Canada : taxonomy and biostratigraphic significance - McLean, Ross A. (NRC Press, 2004)
Rugose corals of the Family Phillipsastreidae are abundant, diverse, and geographically widespread in the Frasnian (lower Upper Devonian) of western Canada.